Critical analysis of the existing and non-existing corporate client’s perspective and response on new launching packages of Carnival internet- Dotlines - Khan, Tanjila (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.